Communications Strategic Intent With Systemigrams: Application to the Network-Enabled Challenge - Blair, Charles; Boardman, John; Sauser, Brian (Systems Engineering, 2007)
The U.K. Ministry of Defense (MoD) has mandated the development of a n etwork enabled capability (NEC) across all of defense, aimed at produc ing agile military and nonmilitary effects via a network of networks. This paper provides an overview of NEC, representing it as a complex h uman activity system of systems (SoS), analysis of which cannot rely o n purely traditional reductionist engineering approaches, requiring in stead a soft-systems engineering approach. A literature review is then provided, covering nontraditional systems methodologies of the past 2 5 years, highlighting the more recent trend towards multimethodologica l practice. The paper introduces the systemic diagram, or systemigram, conceptual model, explaining its evolution from a form of visual lang uage to its use as an appreciative learning system in a soft-systems m ethodology. Using the written prose of MoD policy makers, a systemigra m model is constructed which represents the NEC concept, providing a s ystemic visualization of its complexity and an elucidation of the key SoS attributes of emergence, hierarchy, and boundary. Finally, the NEC systemigram is used in an example storyboarding technique, demonstrat ing its utility as a platform for stakeholder dialog leading towards a refined model that reflects a deeper understanding of NEC strategy. © 2007 Wiley Periodicals, Inc. Syst Eng 10:309–322, 2007